Response of leaf functional traits to soil nutrients in the wet and dry seasons in a subtropical forest on an island - Zhang, Juanjuan; Liang, Minxia; Tong, Sen; Qiao, Xueting; Li, Buhang; Yang, Qiong; Chen, Ting; Hu, Ping; Yu, Shixiao (Frontiers in Plant Science, 2023)
Introduction Island ecosystems often have a disproportionate number of endemic species and unique and fragile functional characteristics. However, few examples of this type of ecosystem have been reported. Methods We conducted a comprehensive field study on Neilingding Island, southern China. The leaf samples of 79 subtropical forest tree species were obtained and their functional traits were studied in the dry and wet seasons to explain the relationships between plant functional traits and soil nutrients. Results We found a greater availability of soil moisture content (SMC) and nutrients in the wet season than in the dry season. The values of wet season soil available phosphorus (5.97 mg·kg−1), SMC (17.67%), and soil available potassium (SAK, 266.96 mg·kg−1) were significantly higher than those of the dry season. The leaf dry matter content, specific leaf weight, leaf density, leaf total carbon, leaf total nitrogen, leaf total calcium, and the N/P and C/P ratios of leaves were all significantly higher in the dry season than in the wet season, being 18.06%, 12.90%, 12.00%, 0.17%, 3.41%, 9.02%, 26.80%, and 24.14% higher, respectively. In contrast, the leaf area (51.01 cm2), specific leaf area (152.76 cm2·g−1), leaf water content (0.59%), leaf total nitrogen (1.31%), leaf total phosphorus (0.14%), and leaf total magnesium (0.33%) were much lower in the dry season than in the wet one. There were significant pairwise correlations between leaf functional traits, but the number and strength of correlations were significantly different in the dry and wet seasons. The SAK, soil total phosphorus (STP), and pH impacted plant leaf functional traits in the dry season, whereas in the wet season, they were affected by SAK, STP, pH, and NO3− (nitrate). Discussion Both soil nutrients and water availability varied seasonally and could cause variation in a number of leaf traits.